Molecular understanding of the possible mechanisms of oligosaccharide oxidation by cold plasma. Issue 2 (11th October 2022) - Yusupov, Maksudbek; Dewaele, Debbie; Attri, Pankaj; Khalilov, Umedjon; Sobott, Frank; Bogaerts, Annemie
Abstract: Cold atmospheric plasma (CAP) is a promising technology for several medical applications, including the removal of biofilms from surfaces. However, the molecular mechanisms of CAP treatment are still poorly understood. Here we unravel the possible mechanisms of CAP‐induced oxidation of oligosaccharides, employing reactive molecular dynamics simulations based on the density functional‐tight binding potential. Specifically, we find that the interaction of oxygen atoms (used as CAP‐generated reactive species) with cellotriose (a model system for the oligosaccharides) can break structurally important glycosidic bonds, which subsequently leads to the disruption of the oligosaccharide molecule. The overall results help to shed light on our experimental evidence for cellotriose oxidation by CAP. This study provides atomic‐level insight into the onset of plasma‐induced removal of biofilms, as oligosaccharides are one of the main components of biofilm. Abstract : Possible mechanisms of cold atmospheric plasma (CAP)‐induced oxidation of cellotriose, as a model system for oligosaccharide (one of the main biofilm components) were studied using reactive molecular dynamics simulations and the results were compared with experiments. It was found that the oxidation of cellotriose leads to the addition of an O atom to the molecule, as well as to the dissociation of its glycosidic bonds. Our simulation results are consistent with our and other experimental results on oligosaccharides.